Damage characterization and resilience optimization of reinforced concrete bridge piers under vehicle impact - Roy, Suman; Unobe, Ikwulono D.; Sorensen, Andrew (Advances in bridge engineering, 2022)
Vehicle impact creates a dynamic loading condition at high strain rate exhibiting a unique interaction with the resisting structural members’ material properties. This interaction results in an increase in the material’s strength properties, a behavior captured in analysis via the computation of a strength factor known as the dynamic increase factor (DIF). In reinforced concrete (RC) bridge piers, the concrete cover receives the initial impact from the vehicle, causing damage to this exterior surface. This makes the DIF related to the concrete material (i.e., the compressive DIF) particularly important in this initial phase of the crash scenario; thus, requiring an in-depth analysis into its effect on the performance of the pier during and after the impact event. This study initiates an investigation into the influence of the compressive DIF on the performance of RC piers under impact from vehicles classes. Of particular interest is estimating a post impact residual capacity for the pier, while also determining concrete strength parameters (compressive strength) that offers a good tradeoff between the shear capacity which primarily resists the impact loads, and the axial capacity which controls the principal serviceability of the pier. The resulting analyses, using a representative test pier, show that an optimal compressive strength of concrete will minimize loss in the residual capacity of the pier. The effect of the compressive DIF on other important design parameters, i.e., bond strength and development length is also scrutinized. This study will aid forensic structural engineers in scrutinizing the post impact concrete behavior and serviceability.